Photogrammetry applied to graphic survey in rehabilitation projects: case study of a detached house. - Alexander Martín-Garín; Iñigo León-Cascante; Jose Javier Pérez-Martínez; Rafael Martín-Talaverano; Amaia Casado; Jose Antonio Millán-García (Anales de Edificación)
This communication analyzes the work carried out for the graphic survey of a case study during its rehabilitation process. For this, the photogrammetry technique has been used together with an RPAS system for the acquisition of photographs of the property. As a result, a point cloud has been obtained that allows the geometric characterization of the analyzed case study. The use of both techniques has proven to be a very useful combination in the field of architecture and rehabilitation processes thanks to the possibility it offers for massive data capture and its subsequent use for the development of the architectural model. This analysis has allowed verifying the advantages and disadvantages of the methodology followed in the study compared to conventional methods of architectural survey